THE AESTHETIC REGIME IN THE MODERN ERA: ART AND DISCOURSE ON ART - Olha T. Bandrovska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article traces the changes in the aesthetic conventions of Modern art in accordance with the dynamics of literary development in Great Britain. The study focuses on three key areas: the impact of “the ancients and moderns” quarrel on European philosophical and literary thought; the nuances of critical and literary discourse in Enlightenment-era Great Britain; and the reception of the Enlightenment aesthetic values and novelties in Victorian criticism, linking them to the emergence of twentieth-century modernism. The subject involves the evolution of Enlightenment aesthetics and poetics in Great Britain, particularly the departure from classical art and literature models, and the emergence of concepts like imagination, novelty, and the reader’s subjective experience of art. Seminal literary-critical essays of the eighteenth century, including works by Joseph Addison, Henry Home, Richard Hurd, and Leslie Stephen’s monograph ‘History of English Thought in the Eighteenth Century”, are analyzed. The paper also examines philosophical texts by Michel de Montaigne, Francis Bacon, René Descartes, and Marquis de Condorcet to understand the oscillatory nature of philosophical thought before and during the Age of Enlightenment. The study contextualizes “the ancients and moderns” debate on models for literary excellence and accentuates its role in shaping the discourse of aesthetics and artistic creativity. Contributions by Enlightenment figures such as Addison, Home, and Hurd are explored, emphasizing how they reshaped the discourse of aesthetics by redefining the nature of beauty, the sublime, and the principles of artistic criticism, thereby influencing the literary and artistic productions of their time and beyond. Particular attention is paid to the critical views of Stephen who wrote about the “fluctuating mode” of the literature of the second half of the eighteenth century, illustrating his peculiar subjectivism as an exponent of the Victorian worldview (Stephen saw Sterne’s novels as a serious moral threat), and simultaneously reflecting the normative aesthetic views of the second half of the nineteenth century. The paper also demonstrates how the antinomianism in aesthetic thinking, which challenged traditional norms and values as seen in “the ancients and moderns” quarrel, was further evolved in the works of Friedrich Schiller and Friedrich Schlegel, the latter articulating the antinomy of “classic versus romantic”. This tradition of antinomian thinking, coupled with the rejection of the idea of linear progression in cultural evolution, a call for a reassessment of values amidst a paradigm shift in culture and the breakdown of traditional ethic and aesthetic systems, finds a notable and unique expression in Friedrich Nietzsche’s works, that significantly influenced the transition from Modernity to Postmodernity. In summary, it is argued that the Modern Age was the time of the emergence of a new aesthetic sensibility, and its aesthetic pluralism and anti-classical literary ideas were pivotal in redefining concepts of progress, novelty, and human consciousness in art and literature. This laid the groundwork for modernist art and literature, characterized by a departure from tradition and a quest for new artistic expressions of human experience.